The Role of Sports Directors, Politicians, Professors, Coaches and P. E. Teachers in NEP of India - Mirant B. Italia (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The National Education Policy (NEP) of India seeks to revolutionize the educational sector by prioritizing holistic growth, skill enrichment, and inclusivity. This academic study delves into the unique and interlinked functions performed by sports directors, politicians, academics, coaches, and physical education instructors in executing and advancing the NEP. Their combined practice to play a pivotal role in shaping policies, crafting syllabi, improving sports facilities, and fostering student involvement in physical training. an examination of their duties and impact, this paper underscores the significance of collaborative efforts among various stakeholders in realizing the goals set forth by the NEP.